Economies of Scope, Resource Relatedness, and the Dynamics of Corporate Diversification - Sakhartov, Arkadiy V. (Strategic Management Journal, 2017)
Research summary: T he dominant view has been that businesses that are more related to each other are more often combined within diversified firms. This study uses a dynamic model to demonstrate that, with inter‐temporal economies of scope, diversified firms are more likely to combine moderately related businesses than the most‐related businesses. That effect occurs because strong relatedness reduces redeployment costs and makes firms redeploy all resources to better performing businesses. The strength of that effect depends on inducements for redeployment measured as the current return advantage of one business over another business, volatilities of business returns, and correlation of those returns. This study develops hypotheses for those relationships and suggests empirical operationalizations, encouraging empiricists to retest the implications of relatedness for the dynamics of corporate diversification . Managerial summary: I t is believed that diversified firms are more likely to combine more‐related businesses because relatedness enables sharing of resources between businesses. Indeed, a firm can apply knowledge created in one business to another business, avoiding costly duplication in knowledge development. Resource sharing also adds value when a firm offers several products, adding the convenience of one‐stop shopping and charging higher prices. However, resource sharing is not the only motivation for corporate diversification. In environments where profitability of businesses changes frequently, firms diversify by redeploying part of resources from an underperforming business to a better performing business. This study uses a dynamic model to demonstrate that, with that second motivation for corporate diversification, firms end up combining moderately related businesses rather than the most‐related businesses . Copyright © 2017 John Wiley & Sons, Ltd.